Believe it or not? : a field study of the perceived credibility of strongly and weakly-branded print and Internet sources. - Goh, Sek Hong. (2008)
Internet sources usually have less credibility than sources using conventional media. Using brand-name as a mediator of credibility,it was found that no differences exist for Internet and conventional media for strong brands but a difference exists for weak brands